Transcriptional changes associated with recurrent airway obstruction in affected and unaffected horses - Venugopal, Changaram S.; Mendes, Luiz Claudio Nogueira [UNESP]; Peiró, Juliana Regina [UNESP]; Laborde, Susan S.; Stokes, Ashley M.; Moore, Rustin M. (Amer Veterinary Medical Assoc, 2010)
Objective-To identify differentially expressed genes in pulmonary tissues of horses affected with summer pasture-associated obstructive pulmonary disease (SPAOPD), which is a form of recurrent airway obstruction (RAO), compared with those of unaffected horses.Animals-6 horses with SPAOPD-RAO and 6 unaffected (healthy) horses.Procedures-Horses were assigned to 2 groups on the basis of medical history, clinical score, and transpleural pressure. Total RNA from each of the 5 lung lobes of each of the 6 SPAOPD-RAO-affected horses was extracted and pooled. Similarly, total RNA from unaffected horses was pooled. Differential display (DD) PCR assay was performed, and differentially expressed bands were purified and cloned into a plasmid vector. Plasmids were extracted from recombinant colonies, and purified DNA was sequenced. Genes of interest for RAO pathogenesis were identified. Real-time PCR assay was performed to confirm findings for the DD PCR assay.Results-18 differentially expressed genes (17 upregulated and 1 downregulated) were identified. Three genes of particular interest were found to be altered (2 upregulated and 1 downregulated) in horses with SPAOPD-RAO by use of real-time FOR assay, and these findings matched the differential expression found by use of the DD PCR assay.Conclusions and Clinical Relevance-SPAOPD-RAO in horses is a multifactorial, complex disease involving several genes. Upregulated genes, particularly beta 2-microglobulin, and the downregulated secretoglobin gene can serve as marker genes that may help to identify SPAOPD-RAO at an early age. (Am J Vet Res 2010;71:476-482)